2012
DOI: 10.1136/bcr.02.2012.5730
|View full text |Cite
|
Sign up to set email alerts
|

1-  hydroxylation defect in postural orthostatic tachycardia syndrome: remission with calcitriol supplementation

Abstract: A 37-year-old woman presented with a history of reactive hypoglycaemia, non-classic adrenal hyperplasia (NCAH), osteopenia and fibromyalgia. After several months of palpitations, postural orthostatic tachycardia syndrome (POTS) was diagnosed by tilt table studies. Her heart rate (HR) reached 191 bpm at 60 degrees from horizontal. Investigation suggested increase in epinephrine and norepinephrine levels in response to tilt table. Her 25(OH) vitamin D level measured by immunoextraction radioimmunoassay was 35 pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, treatment of the underlying and comorbid conditions, if discovered, may significantly improve or completely resolve the autonomic disorder as it is sometimes observed in patients with POTS associated with vitamin deficiencies and autoimmune disorders. 1013 In this case series, a search for an underlying disorder revealed rare or unexpected diseases that would’ve been missed if the diagnostic investigation ended with the diagnosis of POTS and neurogenic orthostatic hypotension. Furthermore, autonomic dysfunction completely resolved in the case of Fabry disease and carcinoid tumor and improved significantly in the patient with Hodgkin’s lymphoma when these disorders were treated with targeted therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, treatment of the underlying and comorbid conditions, if discovered, may significantly improve or completely resolve the autonomic disorder as it is sometimes observed in patients with POTS associated with vitamin deficiencies and autoimmune disorders. 1013 In this case series, a search for an underlying disorder revealed rare or unexpected diseases that would’ve been missed if the diagnostic investigation ended with the diagnosis of POTS and neurogenic orthostatic hypotension. Furthermore, autonomic dysfunction completely resolved in the case of Fabry disease and carcinoid tumor and improved significantly in the patient with Hodgkin’s lymphoma when these disorders were treated with targeted therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Currently, a large number of studies have shown an important association between VD deficiency and ANS activity. For example, Chaudhari et al found that patients with postural standing tachycardia syndrome had lower levels of ossified triol (1,25(OH)D 3 ) than normal subjects and that appropriate supplementation improved patient symptoms, revealing that VD inhibits autonomic nervous system dysfunction in the body [ 13 ]. A clinical study reported that cardiac autonomic function was impaired in people with VD deficiency despite the absence of overt cardiac involvement and symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%